METHODOLOGY OF CONCEPT AND CONCEPTUAL ANALYSIS - 1Babanazarova Sokhiba Abdusharipovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses cognitive linguistics, one of the areas of the anthropocentric paradigm. The views of world linguists on the concept and its types, methods of conceptual analysis are analyzed. The methods of conceptual analysis are explained by means of comparisons. It is well known that man's knowledge of the surrounding world is expressed through concepts. These concepts are a mental-intellectual structure embodied as a product of various mental activities of man. In the process of thinking, a person deals with concepts, not with meanings and notions.Therefore the concept is recognized as a unit of thought and set of knowledge that branched and unified at one point. The article contains stable comparisons in the Uzbek language for conceptual analysis and it is repeatedly acknowledged that the comparisons reflect national and cultural connotations, richness of Uzbek language, and as well as its importance as a mirror of traditions. The analysis focuses on the standard of comparison, which reflects the uniqueness of people's perception and understanding of the world. Therefore, the study of cognitive analysis in relation to comparisons is one of the essential problems of anthropocentric linguistics.